Product market integration and income taxation: distortions and gains from trade - Torben M. Andersen; Allan Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2007)
It is widely perceived that globalization is a threat to tax financed public sector activities. The argument is that public activities (public consumption and transfers) financed by income taxes may distort labour markets and cause higher wages and thus a loss of competitiveness. If the importance of the latter effect is reinforced by globalization, it is inferred that the marginal costs of public funds increase and a retrenchment of the public sector follows. We consider this issue in a Ricardian trade model in which production and specialization structures are endogenous. Even though income taxation unambiguously worsens wage competitiveness, it does not follow that tax distortions or marginal costs of public funds increase with product market integration. The reason is that gains from trade tend to reduce both. Moreover, non-cooperative fiscal policies do not have a bias towards retrenchment due to a positive terms of trade effect from taxation.
Keywords: H2; F1; J22; 330; labour taxation; open economy; policy spill-over; marginal costs of public funds; Einkommensteuer; Marktintegration; Außenhandelsliberalisierung; Makroökonomischer Einfluss; Öffentlicher Sektor; Komparativer Kostenvorteil; Allgemeines Gleichgewicht; Theorie